Popularity: Does it magnify associations between popularity prioritization and the bullying and defending behavior of early adolescent boys and girls?. Issue 2 (10th August 2016) - Duffy, Amanda L.; Penn, Sarah; Nesdale, Drew; Zimmer‐Gembeck, Melanie J.
Abstract: We investigated the contribution of popularity, popularity prioritization, and gender to the explanation of bullying and defending behavior. Participants were 191 early adolescents (124 girls and 67 boys), aged from 10.9 to 13.6 years. Results revealed that adolescents high on popularity were more likely to bully others. Greater popularity prioritization was also associated with more bullying among boys with high levels, and girls with low levels, of popularity. In addition, popularity was positively related to defending among girls, but not boys. Lower popularity prioritization also contributed to greater defending overall. The implications of these findings for understanding bullying and defending are discussed.